EVALUATION OF ANTIBACTERIAL ACTIVITY OF METHANOLIC LEAVE EXTRACT AND FRACTIONS OF BALSAM APPLE (Mormodica balsamina) AGAINST SALMONELLA TYPHIMURIUM AND STAPHYLOCOCCUS AUREUS (FUDMA JOURNAL OF SCIENCES, 2023)
Microorganisms have evolved defence mechanisms against antibacterial agents and are resistant to some antibiotics. The purpose of this study was to evaluate the antibacterial activity of methanolic leaves extract and fractions of M. balsamina against Salmonella typhimurium and Staphylococcus aureus. Four different solvents (hexane, ethyl acetate, n-butanol and residual) fractions of methanolic extract of M. balsamina were tested for antibacterial activity using agar well diffusion method against Salmonella typhimurium and Staphylococcus aureus. Fractions were isolated using Column Chromatography and Fourier Transform Infra-red Spectroscopy (FTIR) was used to detect the characteristic peak values and their functional groups present in the specific fraction that exhibited potent antibacterial activity. The results highlighted that the n-butanol fraction was active against all isolates with maximum zone (19.50±2.12mm) at 100mg/ml while hexane, and ethyl acetate fractions were not active at all concentrations. Phytochemicals investigation showed that saponins and flavonoids were present in large quantity. Further assessment of minimum inhibitory concentration and minimum bactericidal concentration ranged between 3.125 to 50 mg/ml respectively. Fourier Transform Infra-red (FTIR) Spectra of fraction C revealed the presence of different functional groups ranging from carboxylic (R-C (O)-OH), alkanes (C-H), aldehydes (R-CH=O) and alkenes (RCH=CH2), Amides (R-C(O)-NH2), Alkyl halides(R-F), Alcohol (Ar-OH), Ethers (Ar-o-R), and Aromatic (C-H) respectively. The presence of bioactive secondary metabolites, low Minimum Inhibitory Concentration and low Minimum Bactericidal Concentration may justify the traditional uses of the leaves of Mormodica balsamina for therapeutic purposes. FTIR graphs provided characteristic peaks which represented the components responsible for antibacterial activity
Keywords: Mormodica balsamina, Fractionation, Antibacterial, Minimum Inhibitory Concentration, Maximum Bactericidal Concentration and Furrier Transform Infra-red